The impact of psychological traits on performance under pressure - experimental evidence of handball penalties - Bühren, C.; Träger, L. (Journal of Sports Economics, 2022)
Our field experiment analyzes the influence of psychological traits on performance in sequential games. It uses handball penalties thrown under individual, team, or tournament incentives in the ABBA sequence. Considering the single moves of these games, player A and player B are taking turns in being the first-mover. We find no significant first-mover advantage. However, we observe that player A performs better than player B under tournament incentives and if he or she is confident enough.